2008
DOI: 10.1371/journal.pgen.1000307
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Screen to Identify Promoters Conferring High Levels of Phenotypic Noise

Abstract: Genetically identical populations of unicellular organisms often show marked variation in some phenotypic traits. To investigate the molecular causes and possible biological functions of this phenotypic noise, it would be useful to have a method to identify genes whose expression varies stochastically on a certain time scale. Here, we developed such a method and used it for identifying genes with high levels of phenotypic noise in Salmonella enterica ssp. I serovar Typhimurium (S. Typhimurium). We created a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 28 publications
1
62
0
Order By: Relevance
“…Salmonella serovar Typhimurium is a food-borne pathogen that after ingestion invades the gastrointestinal epithelia, reaching the mesenteric lymph nodes. It then can establish a systemic infection, replicating in the spleen and liver of the host (35,39,45,49,84). During pathogenesis, bacteria encounter several different microenvironments in the host (10), and several bacteria, including Salmonella serovar Typhimurium, effectively adapt by utilizing HKs (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella serovar Typhimurium is a food-borne pathogen that after ingestion invades the gastrointestinal epithelia, reaching the mesenteric lymph nodes. It then can establish a systemic infection, replicating in the spleen and liver of the host (35,39,45,49,84). During pathogenesis, bacteria encounter several different microenvironments in the host (10), and several bacteria, including Salmonella serovar Typhimurium, effectively adapt by utilizing HKs (5).…”
Section: Discussionmentioning
confidence: 99%
“…This motility was reported previously to not play a role in Salmonella virulence in vivo (53). However, flagella induce inflammation via Tolllike receptor 5 during Salmonella infection of the intestinal mucosa (32,35,77). During its evolution, Salmonella serovar Typhimurium acquired many pathogenicity islands (57).…”
mentioning
confidence: 99%
“…This result is interesting in the light of a series of recent studies reporting phenotypic variation between genetically identical bacteria that live in homogeneous environments (4,9,10,22,24,(26)(27)(28). These differences include cell size, interdivision intervals, gene expression, and behavior.…”
Section: Vol 193 2011 Pole Age Affects M Extorquens Cell Size Andmentioning
confidence: 74%
“…A screen for noisy promoters in Salmonella enterica showed that some proteins, especially flagellar gene products, show high stochasticity (105). By broadening the range of characters such as motility and environmental stress resistance across a population, high gene expression noise can increase the likelihood that some cells within the population are better able to endure environmental transitions (9,31).…”
Section: Phenotypic Variation Within Populationsmentioning
confidence: 99%
“…Consequently, noise reduction mechanisms preserving the fidelity of regulatory signals may evolve in some cellular functions (21,83). This is borne out by the difference in noise between genes in a genome (105).…”
Section: Phenotypic Variation Within Populationsmentioning
confidence: 99%